The bookbinder's guide to love [large type] - Garbera, Katherine (Garbera, Katherine. WiCKed Sisters, 2024)
"As a lonely foster kid, Serafina Conte sought refuge in handmaking journals -- and writing her wishes within their pages. Now, in the quirky new age store she shares with her two best friends, Sera's intentions have paid off. Her journals are in the spotlight -- and rumored to manifest great things. Whether it's witchy skills, real magic, or not, Sera's finally ready to be the leading lady of her life story . . . Until her plot hits a twist. After the death of her mentor, Ford Sitwell, all the loneliness and insecurity of her past returns. The only balm is the box of antique books he left to her. But Ford's suspicious brooding grandson, Wes, is ready to think the worst of her -- and get his grandfather's books back! The first part doesn't bother her. The second? Forget it. Sera won't give Wes the books so easily. But it's clear he's seeking something more, an emotional connection no book can replace. So she offers a deal -- work in her store for six weeks, and in return, she'll help him get closure by sharing memories of his late grandfather. Yes, Wes seems grumpy, but actually he's hot . . . and maybe kind? Deep down? And when desire and vulnerability work their charms, Sera begins to wonder if the best stories aren't the ones you intend, but the ones that take you where you least expected . . ."--